Association between the ERCC1 polymorphism and platinum-based chemotherapy effectiveness in ovarian cancer: a meta-analysis - Ning Tang; Dan Lyu; Yan Zhang; Haiping Liu (BMC Women's Health, 2017)
Abstract Background Ovarian cancer is a prominent public health problem which affects people all around the world. Platinum-based chemotherapy is a common treatment for ovarian cancer, however, the effectiveness of chemotherapy varies from patient to patient. The excision repair cross complementation group 1 (ERCC1) protein may mediate chemotherapy resistance. A meta-analysis was conducted to explore whether platinum-based chemotherapy effectiveness could be attributed to the ERCC1 C19007T polymorphisms. Methods Seven major databases (EMBASE, Web of Science, Pubmed, Springer Link, Chinese National Knowledge Infrastructure (CNKI), EBSCO and Science Direct databases) were searched for eligible studies. Crude odds ratios (ORs) with 95% confidence intervals (CIs) were calculated to evaluate the results. Results In this meta-analysis, 1169 subjects (425 non-responders and 744 responders) from 8 studies were included. The overall OR (C vs. T alleles) using random model was 1.07 (95% CI 0.75-1.52, P = 0.7), which was not statistically significant. Moreover, there was no significant difference in the analysis by race. Conclusion There is no association between the ERCC1 C19007T polymorphism and platinum-based chemotherapy effectiveness in ovarian cancer. The polymorphism did not have a significant impact on platinum-based chemotherapy in non-responders and responders.